Chemical and mineralogical characterization of Aguada Portezuelo pottery from Catamarca, north-western Argentina: PIXE, XRD and SEM-EDS studies applied to surface pre- and post-firing paints, slips and pastes - de la Fuente, Guillermo Adrian (2020)
Particle-induced X-ray emission (PIXE), X-ray diffraction (XRD), electron microprobe analysis (EDS) and scanning electron microscopy (SEM) analytical techniques were used to characterize surface paints in pre- and post-fired Aguada Portezuelo decorated pottery. Surface paintings in black, white, red, brown, burgundy and ochre were analysed. Major, minor and trace elements were detected by PIXE, whereas XRD and SEM-EDS gave information on the main mineral phases and the characteristic morphology for each analysed pigment. The results obtained indicate that the main colour groups can be easily discriminated by PIXE, and they are characterized by only one pigment for each colour: hematite (red) and manganese mineral oxides (black), respectively, whereas white pigments are characterized by calcite, ghelenite and gypsum.